Effects of soil variation between peat soil and mineral soil on fruit quality of pineapple (Ananas Comosus) cultivars: N36 and josapine - Abu Kasim, Amirul Imran; Mohd Kassim, Angzzas Sari (Penerbit UTHM, 2017)
Consumption of pineapple is predicted to increase in the near future in which the demand for continuous supply of the fruit becomes of major interest. This research is focused on finding the influence of growth medium between peat soil and mineral soil to the weight and production of vitamin C and sugar contents of the pineapple fruits. Two cultivars were investigated: N36 and Josapine. The vitamin C is quantified by Iodate Titration and sugar content is analyzed by Digital Refractometer. The chemical soil properties were analyzed by using atomic absorption spectrophotometer at the Soil Analysis Section laboratory from Department Of Agriculture, Malaysia. All data were analyzed statistically through ANOVA by using SPSS. Results indicated that pineapple planted on peat soil produced heavier fruits than those in mineral soil. N36 pineapple reports no significant difference (p < 0.05) of the vitamin C content and the sweetness between different cultivation soil types. However, Josapine pineapples cultivated on mineral soil (FIMA Plantation) produce significantly 115% higher vitamin C content (19.243 ± 7.191 mg∙100g-1), and significantly 30% lower sugar content (5.403 ± 1.721% °Bx) than cultivated on peat soil (Peninsula Plantations). The finding of the soil type’s influence on the fruit quality production is beneficial for pineapple producers and researchers to broaden up the development of pineapple-based products in the long run. The promotion of pineapple nutritional contents is beneficial to increase consumers’ knowledge and awareness on the importance of pineapple consumption especially in Asian regions.